Determination of Activity Concentrations of Natural Radionuclides and Radiation Hazard Indices in the Sediments of Ogun River (2012)
River sediments are known to contain natural radionuclides, the concentrations of which if beyond certain limits can cause adverse health effects. The sediments from Ogun river provide large quantities of sand for construction purposes in Nigeria. Despite this, data are scarce on the natural radionuclides: 40K, 226Ra and 232Th distribution in the river sediments. This work was aimed at determining the spatial distribution of these natural radionuclides and their concentrations in the sediments of Ogun river, and to evaluate the radiological implications on the population living in houses built with the river sediments. A total of 320 sediment samples were randomly collected along the course of the river; 60 in the upper region (Igboho to Idi- Ata; Oyo – Ogun axis), 90 in the middle region (Olopade to Mile 8 Oba; Ogun –Lagos axis) and 170 in the lower region (Abata to Apa Osa; Lagos axis). The number of samples collected in each region was determined by accessibility. The samples were air dried, pulverized and sieved using a 2 mm mesh size. Two hundred and fifty grams of the sieved samples were transferred into plastic containers of uniform sizes, sealed and left for 4 weeks to attain secular radioactive equilibrium. The activity concentrations of the natural radionuclides in the samples were determined using gamma-ray spectrometer comprising 76mm x 76mm NaI(Tl) detector coupled to a multichannel analyser. These concentrations together with standard equations were used to evaluate indoor effective dose rates, radium equivalent, external and internal hazard indices, representative gamma index and Excess Lifetime Cancer Risks (ELCR) and results were compared with available data from India, Egypt and Turkey. Data were analysed using descriptive statistics. The activity concentrations (in Bq/kg) of 40K, 226Ra and 232Th ranged from 371.0 (middle) – 608.0 (lower), 5.6 – 20.4 (middle) and 5.0 (lower) – 23.1 (middle) respectively. These were similar to data from other locations of the world. The upper region of the river indicated no location effect, in the middle and lower regions, significant location effects were observed and these were attributable to industrial activities. The mean annual indoor effective dose rates were 0.31 ± 0.02 mSv (upper), 0.30 ± 0.05 mSv (middle) and 0.33 ± 0.05 mSv (lower region). The radium equivalent activity for upper, middle and lower regions respectively, were 65.16 ± 4.14 Bq/kg, 64.10 ± 10.78 Bq/kg and 71.00 ± 11.78 Bq/kg, while external hazard indices were 0.18 ± 0.01, 0.17 ± 0.03 and 0.19 ± 0.03. Internal hazard indices were and , representative gamma indices were 0.52  0.03, 0.51  0.08 and 0.56  0.09, whereas ELCR values were ,and .,01.021.004.021.005.023.031001.0141.031002.0137.031003.014The radiological hazard indices evaluated for Ogun river sediments were less than acceptable limits and therefore posses no radiation risk on the populations living in the houses built with materials incorporating the river sediments.